(untitled) (Eurasian Research Bulletin, 2022)
Language is traditionally understood as a multi-level system, as a system of systems of phonology, morphology, syntax. The first half of the 20th century in linguistics passed under the banner of structuralism, and then generative grammar. This led to the fact that the level model, largely logical and due to the need to study the structural units of the language, was elevated to the absolute: language levels were perceived as self-sufficient, almost autonomous areas. The response to such a mechanistic approach to language was the formation of a new linguistic paradigm – discourse.